ANALISIS PERKIRAAN KEBUTUHAN PEGAWAI DALAM UPAYA PENCAPAIAN KINERJA ORGANISASI YANG BERKELANJUTAN DENGAN METODE PENDEKATAN ANALISIS REGRESI - Budi Setiawan1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2006)
The application of an analysis method or tool is very critical when facing the power efficiency of the method or tool applied. In this case, there are several methods applicable for measuring the rational number of personnel to be employed. However, to determine whether or not the tool is valid and reliable depends on the ability and practicality of the analysis tool itself. The reliability of the tool is proved when it is continuously tested and used with regard to its strengths and weaknesses. Therefore, in order to be able to measure the rational number of personnel to be employed for the sake of organization’s sustainable performance achievement,this paper proposes a regression analysis. It is hoped this would broaden the knowledge of the readers or researchers who vigilantly keep attention to the human resource management.